2021
DOI: 10.1080/11101849.2021.1955532
|View full text |Cite
|
Sign up to set email alerts
|

Continuous midazolam infusion can minimize the pro-inflammatory response to anesthesia and surgery for pediatric patients with intra-abdominal infection: Comparative study versus continuous propofol infusion

Abstract: F. Atyia (2021) Continuous midazolam infusion can minimize the pro-inflammatory response to anesthesia and surgery for pediatric patients with intra-abdominal infection: Comparative study versus continuous propofol infusion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…A recent 2021 study by Lotfy et al [ 5 ] on a population of pediatric patients with intra-abdominal infection showed that the infusion of Midazolam and not Propofol decreases serum cytokine levels. A series of studies by Lisowska et al [ 9 ] and Marik [ 44 ] have shown that Propofol decreases serum concentrations of IL-1, TNF- α , and IL-6 and increases the concentration of IL-10, so this anesthetic drug may have antioxidant and anti-inflammatory properties.…”
Section: ⧉ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent 2021 study by Lotfy et al [ 5 ] on a population of pediatric patients with intra-abdominal infection showed that the infusion of Midazolam and not Propofol decreases serum cytokine levels. A series of studies by Lisowska et al [ 9 ] and Marik [ 44 ] have shown that Propofol decreases serum concentrations of IL-1, TNF- α , and IL-6 and increases the concentration of IL-10, so this anesthetic drug may have antioxidant and anti-inflammatory properties.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…As an anesthetic drug, Midazolam is used in premedication and procedural sedation. Midazolam can minimize the proinflammatory response to anesthesia [ 5 ]. It seems that Midazolam can induce apoptosis and can suppress the progression of cancer cells, having antitumorigenic properties, which should be considered in choosing the anesthetic drug [ 6 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%